Study on national accounts in the ESCWA region sources and methods - United Nations. Economic and Social Commission for Western Asia. Statistics Division (New York United Nations, 2009)
"This study, produced by the Statistics Division at the Economic and Social Commission for Western Asia (ESCWA), is a review of the sources and methods used in the compilation of National Accounts in the region. Its main aim consists in setting a baseline for the Statistic Division's plan of action to increase ... the statistics capacities of member countries in the estimation of high-quality National Accounts data and comply with the latest international standards and recommendations of the System of National Accounts. The content of the study is mainly based on the information collected through the responses to a questionnaire designed by the ESCWA."--P. iii.
Cover title.
At head of title: Economic and Social Commission for Western Asia (ESCWA).
Electronic version is also available via the Official Document System of the United Nations. Address: http://documents.un.org.
Keywords: National income -- Accounting. -- Middle East